Internalization of Erythrocyte Acylpeptide Hydrolase Is Required for Asexual Replication of Plasmodium falciparum - Rubayet Elahi (American Society for Microbiology, 2019)
ABSTRACT The human malaria parasite Plasmodium falciparum causes disease as it replicates within the host’s erythrocytes. We have found that an erythrocyte serine hydrolase, acylpeptide hydrolase (APEH), accumulates within developing asexual parasites. Internalization of APEH was associated with a proteolytic event that reduced the size of the catalytic polypeptide from 80 to 55 kDa. A triazole urea APEH inhibitor, termed AA74-1, was employed to characterize the role of parasite-internalized APEH. In cell lysates, AA74-1 was a potent and highly selective inhibitor of both host erythrocyte and parasite-internalized APEH. When added to cultures of ring-stage parasites, AA74-1 was a poor inhibitor of replication over one asexual replication cycle; however, its potency increased dramatically after a second cycle. This enhancement of potency was not abrogated by the addition of exogenous isopentenyl pyrophosphate, the sole essential product of apicoplast metabolism. High-potency inhibition of parasite growth could be effected by adding AA74-1 to schizont-stage parasites, which resulted in parasite death at the early trophozoite stage of the ensuing replication cycle. Analysis of APEH inhibition in intact cultured cells revealed that host erythrocyte APEH, but not the parasite-internalized APEH pool, was inhibited by exogenous AA74-1. Our data support a model for the mode of parasiticidal activity of AA74-1 whereby sustained inactivation of host erythrocyte APEH is required prior to merozoite invasion and during parasite asexual development. Together, these findings provide evidence for an essential catalytic role for parasite-internalized APEH. IMPORTANCE Nearly half a million deaths were attributed to malaria in 2017. Protozoan parasites of the genus Plasmodium cause disease in humans while replicating asexually within the host’s erythrocytes, with P. falciparum responsible for most of the mortality. Understanding how Plasmodium spp. have adapted to their unique host erythrocyte environment is important for developing malaria control strategies. Here, we demonstrate that P. falciparum coopts a host erythrocyte serine hydrolase termed acylpeptide hydrolase. By showing that the parasite requires acylpeptide hydrolase activity for replication, we expand our knowledge of host cell factors that contribute to robust parasite growth.